SURGERY THERAPY MANAGEMENT OF GINGIVAL RECESSION. A SYSTEMIC REVIEW - Silvia Martu (Romanian Dental Association for Education, 2015)
Gingival recession is defined as the apical migration of the jonctional epithelium with exposure of root surfaces. It is a common condition seen in both dentally aware populations and those with limited access to dental care. The etiology of the condition is multi factorial but is commonly associated with underlying alveolar morphology, tooth brushing, mechanical trauma and periodontal disease. Given the high rate of gingival recession defects among the general population, it is imperative that dental practitioners have an understanding of the etiology, evolution, complications and the therapy management of the condition. Numerous therapeutic solutions for recession defects have been proposed in the periodontal literature and modified with time according to the evolution of clinical knowledge. Careful case selection and surgical management are critical if a successful outcome is to be achieved.